Papilla Height as an Objective Parameter to Measure Gingival Biotype - Mandaloy, Akash; Sridhar, Raja; Singh, Abhilasha; Shirahatti, Ravi (The Journal of Dentists, 2016)
Background: There is lack of objective criteria to classify gingival biotype. The aim of the present study is to establish the papillary length - a surrogate parameter, as an objective criterion to classify periodontal biotype as thick or thin in periodontally healthy subjects. Methods: In 76 periodontally healthy subjects gingival thickness was assessed by probe transparency at the midfacial aspect of both maxillary central incisors. The papillary length between the two central incisors (PL sum 1), the sum of papillary length between central and lateral incisor on either side and between the two central incisors (PL sum 3), the sum of papillary length between canine and lateral incisor, central and lateral incisor on both sides and between the two central incisors (PL sum 5) was calculated. The data so obtained were subjected to statistical analysis to find a correlation between PL sum scores and gingival biotype. Results: PL sum scores displayed larger PL sum scores for thin biotype group as compared to thick biotype group wherein the mean PL sum 1 score was 4.53 and 4.49mm and PL sum 5 score was 21.8 and 19.83 for thin and thick biotype groups respectively. The difference in the mean PL sum scores for PL sum 1, 3, and 5 were not significant between thick and thin gingival biotypes. According to the binary logistic regression analysis, age was the only significant predictor of gingival biotype (thick/thin). Gender as well as different calculations of PL sum scores had no significant effect on the gingival biotype as outcome. A part of the variation obtained in the biotype was predicted by the sum scores though with a weak canonical correlation of 0.37. Conclusion: Scores of PL may be used as an objective parameter to assess the gingival biotype of patients which is a variable needed to be evaluated prior to restorative or surgical treatment procedures in order to gain a favourable treatment outcome.